Porcine intestinal submucosa extracellular matrix patch rupture after carotid endarterectomy - Georgios S. Sfyroeras, MD; Constantinos N. Antonopoulos, MD; Andreas Panagiotopoulos, MD; Konstantinos G. Moulakakis, MD; Andreas M. Lazaris, MD; John D. Kakisis, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Porcine intestinal submucosa extracellular matrix (SIS-ECM) patches have shown promise as superior alternatives to synthetic materials for carotid endarterectomy. However, in the pressurized arterial environment, the mechanical strength of SIS-ECM patches may diminish during the remodeling process. This degradation can result in patch rupture and pseudoaneurysm formation. We report the case of a 77-year-old patient who experienced a rupture of the SIS-ECM patch 2 months post- carotid endarterectomy. The patient was successfully treated with saphenous vein patch reconstruction, resulting in a favorable outcome.